Adherence in Pulmonary Tuberculosis Patients Based on King’s Interacting Systems Theory - Tintin Sukartini; Ratna Sitorus; Agung Waluyo; Ede Surya Darmawan (Universitas Airlangga, 2015)
Introduction: Indonesia is one of largest contributor countries to pulmonary TB cases in the world. One of the factors that cause it is no adherence in the treatment. It is necessary to develop a model in order to improving compliance in patient. For an initial step, it is necessary to explore patient’s adherence that based on King’s interacting systems theory. The objective of this study was to explore the patients experience that cause them obedient the treatment based on King’s interacting systems theory.Method: This research was a qualitative research with descriptive explorative approach. The samples were selected through purposive sampling method. Participants in this study were 8 patients who met the inclusion criteria. In this study, participants were pulmonary TB patients who have undergone treatment for 5-6 months.Results: There were 12 themes in patients compliance based on King’s interacting systems theory; (1) true perception of pulmonary tuberculosis, (2) self-awareness, (3) optimal growth and development, (4) positive self-image, (5) a healthy environment, (6) discipline to take medication, (7) effective coping, (8) open communication with the patient's health workers and family, (9) to perform its role optimally, (10) balancing stress during illness, (11) knowing the health care bureaucracy and (12) able to take decisions.Discussion: The 12 themes describe that adherent patients have interaction systems that were personal systems, interpersonal systems and social systems.